2006
DOI: 10.1590/s1678-77572006000100010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of apical microleakage using different root-end filling materials

Abstract: The objective of this study was to evaluate the apical leakage of retrograde cavities filled with Portland Cement (Concrebrás S/A-MG-Brazil), ProRoot MTA™ (Dentsply International, Johnson City, TN, USA) and Sealapex (Kerr Corporation, Orange, California, USA) with addition of zinc oxide (Odahcam Herpo Produtos Dentários Ltda, Rio de Janeiro, RJ, Brazil). Forty-two extracted single-rooted human teeth were decoronated and used for this study. The root canals were instrumented at 1.0mm short of the apical foramen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…Sealapex + zinc oxide and ZOE gave the best results in microbial leakage prevention as root-end fillings compared with MTA and Portland cement (both gray and white presentations) at all time intervals. In other investigation, using dye penetration in extracted human teeth, Valera et al (22) observed no statistical differences among the levels of the marginal infiltration of Sealapex + zinc oxide, MTA and Portland cement. MTA, Portland cement and Sealapex have been shown to induce hard tissue deposition in previous studies (9,10,14,23).…”
Section: Discussionmentioning
confidence: 84%
“…Sealapex + zinc oxide and ZOE gave the best results in microbial leakage prevention as root-end fillings compared with MTA and Portland cement (both gray and white presentations) at all time intervals. In other investigation, using dye penetration in extracted human teeth, Valera et al (22) observed no statistical differences among the levels of the marginal infiltration of Sealapex + zinc oxide, MTA and Portland cement. MTA, Portland cement and Sealapex have been shown to induce hard tissue deposition in previous studies (9,10,14,23).…”
Section: Discussionmentioning
confidence: 84%
“…Inadequate filling and obturation might result in penetration of fluids into the voids, inducing a periapical chronic inflammatory reaction and interfering the treatment success (16). …”
Section: Resultsmentioning
confidence: 99%
“…This was further supported by Torabinejad et al .,[12] who concluded that hydration of the powder might have resulted in formation of the colloidal gel that solidified to a hard structure in less than 4 h. Least microleakage was shown by MTA in the present study, which is also in accordance to some other study conducted in Brazil. [15]…”
Section: Discussionmentioning
confidence: 99%